CONCEPTUAL FOUNDATIONS OF CADETS LEADERSHIP QUALITIES IN THE CONTEXT OF MODERN MILITARY EDUCATION (Psychology Travelogs, 2025)
The article explores the conceptual foundations of developing leadership qualities among cadets within modern military education. In the context of dynamic changes in the security environment and increasing demands on military personnel, the development of leadership potential is viewed as a key prerequisite for the professional readiness of future officers. Military leadership is considered a multidimensional construct, encompassing motivational, cognitive, communicative, and managerial components that enable effective performance in complex and stressful conditions.The theoretical analysis emphasizes an integrative approach combining pedagogical, psychological, and organizational factors. Individualized educational strategies that account for personal traits, professional aspirations, and the specifics of military training play a significant role, promoting the formation of stable leadership behaviors aligned with contemporary service standards.The empirical part evaluates the development of key components of cadets’ leadership potential. Results confirm the heterogeneous nature of leadership formation: a significant proportion of cadets demonstrate medium or high levels of achievement motivation, self-efficacy, and communicative competence, while some show underdeveloped leadership characteristics, inconsistent management styles, and reduced attention stability.The study highlights the need for purposeful development of leadership competencies within professional military training, including fostering resilience, decision-making skills, emotional regulation, teamwork, and responsibility. Reflective practices, real-life scenario modeling, and a supportive educational environment encourage cadets’ autonomy and initiative.The conclusions underscore that leadership development is a systematic pedagogical task. Strengthening leadership qualities ensures the effectiveness of future officers and enhances the overall operational capability of the Armed Forces. The article provides theoretical justifications and practical recommendations for optimizing programs aimed at enhancing leadership potential in military institutions.
Keywords: leadership; leadership qualities; military education; military unit